2020
DOI: 10.1161/hypertensionaha.120.15292
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Hypertension in Turner Syndrome During a 12-Year Pragmatic Interventional Study

Abstract: Turner syndrome is caused by complete or partial X monosomy in some or all cells. Cardiovascular complications are dominant, including increased blood pressure (BP), leading to early-onset hypertension. The aim is to describe the debut, development, and treatment of hypertension in Turner syndrome during a 12-year pragmatic interventional study to help identify risk factors associated with hypertension. One hundred and two women (aged 38±11 years, range: 18–62 years) with Turner syndrome verified by karyotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Patients with TS develop hypertension at an early age, and observational studies have reported that the prevalence of hypertension is between 21 and 40% in girls and adolescent females with TS [15][16][17]. A similar pattern in which the prevalence of hypertension increases with age in essential hypertension is also observed in TS [18,19]. A pragmatic, observational 12-year study, of 102 women age 18-62 years, followed for 12 years, demonstrated that age was positively associated with systolic BP: 53% of participants were treated with antihypertensive medication at the end of the study, an increase of 24% over the duration of the study [19].…”
Section: Introductionmentioning
confidence: 74%
“…Patients with TS develop hypertension at an early age, and observational studies have reported that the prevalence of hypertension is between 21 and 40% in girls and adolescent females with TS [15][16][17]. A similar pattern in which the prevalence of hypertension increases with age in essential hypertension is also observed in TS [18,19]. A pragmatic, observational 12-year study, of 102 women age 18-62 years, followed for 12 years, demonstrated that age was positively associated with systolic BP: 53% of participants were treated with antihypertensive medication at the end of the study, an increase of 24% over the duration of the study [19].…”
Section: Introductionmentioning
confidence: 74%
“…However, it is crucial for treating physicians to be aware of the importance of standardised BP measurement in this group of patients with increased risk of CVD as well as adhesion to guidelines recommending BP measurements at every visit already in childhood to identify hypertension earliest possible. High BP during routine care should alarm clinicians to organise a thorough follow‐up with 24‐h ambulatory BP monitoring to distinguish between white coat and essential hypertension 17 . A recent study showed that without initiation of antihypertensive medication BP increased steadily throughout adulthood in patients with TS while antihypertensive treatment effectively lowered BP, underlining the importance of early intervention with lifestyle changes and medication according to guidelines, if hypertension is diagnosed 3,7,17 …”
Section: Discussionmentioning
confidence: 99%
“…High BP during routine care should alarm clinicians to organise a thorough follow‐up with 24‐h ambulatory BP monitoring to distinguish between white coat and essential hypertension 17 . A recent study showed that without initiation of antihypertensive medication BP increased steadily throughout adulthood in patients with TS while antihypertensive treatment effectively lowered BP, underlining the importance of early intervention with lifestyle changes and medication according to guidelines, if hypertension is diagnosed 3,7,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following acquired and potentially severe cardiovascular complications may be observed: hypertension, aortic dilation (aneurysm) with a potential risk of aortic dissection, more rarely, atherosclerosis and cerebrovascular accidents [47][48][49][50][51][52][53][54][55][56]. There is also a high risk of hypertension (HT) from childhood onwards, and HT is reported in about half of all adult patients [57][58][59][60][61]. The main objective of management is to limit aortic dilation and the risk of dissection.…”
Section: Cardiovascular Managementmentioning
confidence: 99%